The Transition. Convergence and discrepancy in the international and national press coverage of Spain’s major postwar international news export - Tulloch, Christopher David; Guillamet Lloveras, Jaume (RIHC. Revista Internacional de Historia de la Comunicación, 2018)
Over the last nine years, the role of the national and international press in the Spanish political transition has been the subject of three consecutive research projects led by the Journalism Research Group at the Universitat Pompeu Fabra in Barcelona: i) the role of the international press and foreign correspondent corps stationed in Spain; ii) the national newspapers' standpoint on political developments at the time and iii) the explosion of the magazine market that accompanied the consolidation of parliamentary democracy. For the first time, this paper attempts to draw across-the-board conclusions based on the results of all three studies carried out by researchers from six universities from all over Spain. The paper analyses the projection of Spain's biggest international story since the Civil War in the international media arena while at the same time considering its effects on local and national press dynamics.